Keynote Address: The Inviolability and Inalienability of Women's Rights - Davide, Jr., Hilario G. (Review of Women's Studies; Vol 12 No 1-2 (2002): Review of Women's Studies Volume XII, Numbers 1-2 (January-December 2002))
Speech delivered during the book launching of Gender Sensitivity in the Court System on 29 July 2002 at the Manila Hotel.